The impact of a training method to develop psychological compatibility and the accuracy of some basic football skills, under age of 19 - Sabaa, Ahmed Auraibi; Mansoor, Basim Jabar; Thabbah, Nasir Kurdi (International Journal of Psychosocial Rehabilitation, 2020)
The researchers studied the importance of football, and the outstanding position it occupies and developments in the team’s playing methods, among these sciences is psychology sciene that has contributions and an effective influential role in this development, due to the great development that has occurred in training science field to the distinguished position taken by football and development of the team’s playing styles in terms of using the best variety of training methods. Lack of interest in the psychological aspect and lack of focus on the performance of basic skills in the (last quarter) of the game time, where it is difficult for players to perform technical duties, as the researchers have approached to this problem. Where the mean, standard deviations, the calculated and tabulated (T) value of the pre and posttests results were presented, in addition to the results discussing. The researchers conclude that the use of the exercises chosen within the training program should have a positive effect in developing self-confidence and the accuracy of some basic football skills of the experimental group. They recommend the necessity of player’s participation in local competitions, the purpose of that is to know the effect of psychological compatibility in improving the performance of the basic football skills.